HLA-DRB1 Class II antigen level alleles are associated with persistent HPV infection in Mexican women; a pilot study - Bernal Silva, Sofía; Granados, Julio; Gorodezky, Clara; Aláez, Carmen; Flores Aguilar, Hilario; Cerda Flores, Ricardo Martín; Guerrero González, Geraldina; Valdez Chapa, Lezmes Dionicio; Morales Casas, José; González Guerrero, Juan Francisco; Barrera Saldaña, Hugo Alberto (2013)
Background: Persistent infection with high-risk human papillomavirus (HPV) is a major risk factor for malignant lesions and cervical cancer. A widely studied element in the search for genetic factors influencing risk HPV infection diseases is allelic variation of the human leukocyte antigen (HLA) locus. The study was designed to search for HLA susceptibility alleles contributing to the persistence of HPV infection in Mexican women. Methods: A total of 172 subjects were divided into three groups: 1) HPV–persistent patients; 2) HPV–cleared; and 3) HPV–reinfected patients. They were screened for HPV types using a polymerase chain reaction (PCR). PCR-sequence specific oligonucleotide probes (PCR-SSOP) was used for HLA DRB1 and DQB1 typing. Results: We observed that HLA-DQB1*0501 allele might be associated with susceptibility of reinfection with HPV (p = 0.01, OR = 4.9, CI 95% = 1.3 -18.7). Allele frequency of HLA-DRB1*14 was particularly reduced in patients with cancer when compared with the HPV–persistent group (p = 0.04), suggesting that this allele is a possible protective factor for the development of cervical cancer (OR = 2.98). HLA-DRB1*07 might be associated with viral clearance (p = 0.04). Conclusions: Genetic markers for HPV infection susceptibility are different in each population, in Mexicans several HLA-DQB1 alleles might be associated with an enhanced risk for viral persistence. In contrast, DRB1*14, seems to confer protection against cervical cancer.